2006
DOI: 10.1152/ajpendo.00498.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes and insulin on betaine-homocysteineS-methyltransferase expression in rat liver

Abstract: Elevation of plasma homocysteine levels has been recognized as an independent risk factor for the development of cardiovascular disease, a major complication of diabetes. Plasma homocysteine reflects a balance between its synthesis via S-adenosyl-L-methionine-dependent methylation reactions and its removal through the transmethylation and the transsulfuration pathways. Betaine-homocysteine methyltransferase (BHMT, EC 2.1.1.5) is one of the enzymes involved in the remethylation pathway. BHMT, a major zinc metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 41 publications
11
75
0
Order By: Relevance
“…These data demonstrate another potential source of the formaldehyde in diabetes that warrants evaluation, and suggest a possible metabolic adaptation that has been unrecognized in the literature. There are studies that have demonstrated upregulation of elements of the methionine cycle (52,66), but these studies were unable to evaluate the entire pathway concurrently and that is a particular strength of the present data.…”
Section: Ajp-endocrinol Metabmentioning
confidence: 87%
“…These data demonstrate another potential source of the formaldehyde in diabetes that warrants evaluation, and suggest a possible metabolic adaptation that has been unrecognized in the literature. There are studies that have demonstrated upregulation of elements of the methionine cycle (52,66), but these studies were unable to evaluate the entire pathway concurrently and that is a particular strength of the present data.…”
Section: Ajp-endocrinol Metabmentioning
confidence: 87%
“…Reduced peripheral resistance to insulin has been con sidered responsible for lower plasma homocysteine lev els in the initial phases of experimental diabetes (26,27), due to increased transsulfuration (28). On the other hand, variations in serum homocysteine levels were not related with insulin, proinsulin, and insulin sensitivity among the Parkatêjê Indians (29).…”
Section: Discussionmentioning
confidence: 99%
“…This shift is also reflected in other 270 gluconeogenic states, such as diabetes. We and others have demonstrated that a diabetic state or 271 administration of synthetic glucocorticoid compounds has a major impact on methyl group and 272 homocysteine metabolism [23][24][25][26][49][50][51][52]. A consistent finding from these reports is a reduction 273 in circulating homocysteine concentrations owing to an increase in folate-independent 274 remethylation (i.e., BHMT) and catabolism of homocysteine through the transsulfuration 275 pathway.…”
mentioning
confidence: 88%